2019
DOI: 10.1088/1741-4326/ab3812
|View full text |Cite
|
Sign up to set email alerts
|

Control of the hydrogen:deuterium isotope mixture using pellets in JET

Abstract: Deuterium pellets are injected into initially pure hydrogen H-mode plasma in order to control H:D isotope mixture. The pellets are deposited in outer 20% of minor radius, similar to that expected in ITER creating transiently hollow electron density profiles. The isotope mixture of H:D ~ 45:55% is obtained in the core with pellet fuelling throughput of Φ = 0.045 , ⁄ similar to previous pellet fuelling experiments in pure deuterium. Evolution of H:D mix in the core is reproduced using simple model although deute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Although there is presently no experimental determination of the required, minimal equilibration time, there are a number of published studies, from present generation tokamaks, from which to get a sense of time scale for this equilibration. These include (a) the JET DTE1 data of [4] in which great agreement is shown between sub-divertor and main plasma measurements (including neutrons) over a very large range of isotopic concentrations, (b) a long-pulse, particle balance study on Tore Supra in which it was specifically shown that the Penning-OGA measurement, in this case in the pumping duct of a toroidal pumped-limiter, was in full agreement with neutral particle analyzer (NPA) data from the core, thus permitting the former to continue taking data over much longer time scales than was possible for the latter diagnostic [19] (see figure 8), and (c) a recent study on JET-ILW, in which the sub-divertor isotopic concentrations match quite well the concentrations measured by the core CXS diagnostic [20]. This should however be checked (via modeling) for ITER, especially since it has already been established that isotopic measurement by divertor spectroscopy will not be feasible at low concentrations, while CXS and NPA may be quite limited in resolving small isotopic concentrations.…”
Section: Relation Between Sub-divertor and Main Plasma Isotopic Contentsupporting
confidence: 70%
“…Although there is presently no experimental determination of the required, minimal equilibration time, there are a number of published studies, from present generation tokamaks, from which to get a sense of time scale for this equilibration. These include (a) the JET DTE1 data of [4] in which great agreement is shown between sub-divertor and main plasma measurements (including neutrons) over a very large range of isotopic concentrations, (b) a long-pulse, particle balance study on Tore Supra in which it was specifically shown that the Penning-OGA measurement, in this case in the pumping duct of a toroidal pumped-limiter, was in full agreement with neutral particle analyzer (NPA) data from the core, thus permitting the former to continue taking data over much longer time scales than was possible for the latter diagnostic [19] (see figure 8), and (c) a recent study on JET-ILW, in which the sub-divertor isotopic concentrations match quite well the concentrations measured by the core CXS diagnostic [20]. This should however be checked (via modeling) for ITER, especially since it has already been established that isotopic measurement by divertor spectroscopy will not be feasible at low concentrations, while CXS and NPA may be quite limited in resolving small isotopic concentrations.…”
Section: Relation Between Sub-divertor and Main Plasma Isotopic Contentsupporting
confidence: 70%
“…This effect is much weaker than with other methods to control the ELM frequency, e.g. pellets [29] ( [30] for D-T) or vertical position kicks [31]. So far, the physics of this is not understood, especially because there is no very significant change in the pedestal top parameters.…”
Section: Elm Bunchingmentioning
confidence: 95%
“…Core isotope ratio control has also been demonstrated by shallow (low penetration) deuterium pellets injected into a plasma simultaneously fuelled by hydrogen gas and hydrogen NBH (Valovic et al . 2019). A core H/D ratio n H / n D ≈ 1.2, close to the target of n H / n D = 1, was obtained despite the different fuelling methods for the two species, as inferred from core hydrogen isotope CXS and from the neutron rates.…”
Section: Isotope Dependence In Jet-ilw Type I Elmy H-modesmentioning
confidence: 99%